2018
DOI: 10.1016/j.ijvsm.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and burden of gastrointestinal helminthes among grey-breasted helmet guinea fowls (Numida meleagris galeata) encountered in Gombe state, Nigeria

Abstract: This cross sectional survey was conducted from July to December 2015 in order to investigate the burden of gastrointestinal helminthes among guinea fowls in Gombe, Northeastern Nigeria. A total of six hundred fowls (viscera) were purchased from six randomly selected slaughter slabs. Out of the 600 birds examined, 479 (79.83%; 95% CI: 76.4, 82.9) were found harbouring one or more gastrointestinal helminthes. Of this, 238 birds (39.7%; 35.8, 43.6) were infected by nematode species and 392 birds (65.3%; 61.4, 69.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
3
0
2
Order By: Relevance
“…Our study revealed that guinea fowls are majorly infected with H. gallinarum and A. galli with moderate to minimal infection rate of R. tetragona , Strongyloides avium , S. trachea , S. brumpti , and Eimeria species. This body of evidence supports previous studies conducted in Nigeria [24, 25].…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that guinea fowls are majorly infected with H. gallinarum and A. galli with moderate to minimal infection rate of R. tetragona , Strongyloides avium , S. trachea , S. brumpti , and Eimeria species. This body of evidence supports previous studies conducted in Nigeria [24, 25].…”
Section: Discussionsupporting
confidence: 92%
“…Gross examination of feces showed result of its consistency, it tells about diarrhea, hard, sandy or soft. Color green can mean parasites, dark brown mean anoxia for about 24 hours and red due to the presence of blood which shows infection in intestines [16].Several studies about intestine parasites had been conducted on wild birds [17][18][19][20][21][22]. Our study revealed the presence of coccidiosis in fecal samples.…”
Section: Discussionmentioning
confidence: 62%
“…Dentre as principais espécies de helmintos albergadas por Numida meleagris a espécie Heterakis gallinarum, foi relatada em casos de infecções que provocaram alta morbidade e mortalidade nas aves [13]. Adicionalmente, Ascaridia galli foi relatado em alta prevalência em Numida meleagris na Nigéria, alcançando até 56,7% dos casos de infecção, embora este parasita seja mais comumente relatado em frangos domésticos [6].…”
Section: Discussionunclassified
“…A elevada carga parasitária de A. galli e H. gallinarum aqui descrita em galinha-d'angola foi o primeiro relato no estado de Rondônia. A alta infestação, possivelmente, foi influenciada pela época de nascimento das pintainhas, uma vez que as altas temperaturas da região amazônica, agregadas à alta umidade em época chuvosa, são fatores preponderantes para a maior incidência destes helmintos, visto que ambas as espécies são mais identificadas na época chuvosa, enquanto coccídeos são mais prevalentes em período de seca [6].…”
Section: Discussionunclassified